The weird and the eerie - Fisher, Mark, 1968-2017 (London : Repeater Books, 2016)
"What exactly are the 'weird' and the 'eerie'? In this new essay, Mark Fisher argues that some of the most haunting and anomalous fiction of the 20th century belongs to these two modes. The 'weird' and the 'eerie' are closely related but distinct modes, each possessing its own distinct properties. Both have often been associated with Horror, yet this emphasis overlooks the aching fascination that such texts can exercise. The 'weird' and the 'eerie' both fundamentally concern the outside and the unknown, which are not intrinsically horrifying, even if they are always unsettling. Perhaps a proper understanding of the human condition requires examination of liminal concepts such as the 'weird' and the 'eerie'. These two modes will be analysed with reference to the work of authors such as H.P. Lovecraft, H.G. Wells, M.R. James, Christopher Priest, Joan Lindsay, Nigel Kneale, Daphne Du Maurier, Alan Garner and Margaret Atwood, and films by Stanley Kubrick, Jonathan Glazer and Christoper Nolan." -- Publisher's description
Introduction : the weird and the eerie (beyond unheimlich) -- The weird. The out of place and the out of time: lovecraft and the weird -- The weird against the worldly: H.G. Wells -- "Body a tentacle mess": the grotesque and the weird: The Fall -- Caught in the coils of ouroboros: Tim Powers -- Simulations and the unworlding: Rainer Werner Fassbinder and Philip K. Dick -- Curtains and holes: David Lynch -- The eerie. Approaching the eerie -- Something where there should be nothing: nothing where there should be something: Daphne du Maurier and Christopher Priest -- On vanishing land: M.R. James and Eno -- Eerie Thanatos: Nigel Kneale and Alan Garner -- Inside out: outside in: Margaret Atwood and Jonathan Glazer -- Alien traces: Stanley Kubrick, Andrei Tarkovsky, Christopher Nolan -- "...The eerieness remains": Joan Lindsay.
boek
Keywords: Fiction -- 20th century -- History and criticism; Horror in literature